Exploring the Viability of NARNIA with Cognitive–Communication Difficulties: A Pilot Study - Whitworth, Anne; Ng, Naomi; Timms, Lydia; Power, Emma (Seminars in Speech and Language, 2020)
Everyday discourse is a common context for the difficulties experienced by people with acquired neurogenic communication disorders. While evidence is present for effective manualized interventions that directly improve the discourse skills in aphasia, this remains limited for people with cognitive–communication disorders. This proof of concept study used an in-depth case series approach to trial the NARNIA discourse intervention used successfully in aphasia to explore transferability of the protocol and effectiveness in people with cognitive–communication impairments. Four female participants with mild to moderate cognitive–communication difficulties (mean age: 52.8 years)—two following traumatic brain injury and two following vascular episodes—were recruited. Modifications were made to the protocol to accommodate the participant group. Cognitive-linguistic abilities, self-perceptions of communicative behavior and psychosocial recovery, and repeated discourse measures were assessed pre-, immediately post, and at 4 weeks following intervention, to measure treatment effectiveness. Significant gains were observed in quantity of output, informativeness, and efficiency of information across both everyday and narrative discourse genres for all participants. However, in contrast to previous studies, minimal change was observed in discourse macrostructure elements. Significant improvements were also observed in memory or working memory for two participants. This study provides preliminary evidence for the effectiveness of using an adapted protocol with people with cognitive–communication disorders, highlighting how adaptations may address the cognitive needs of this diverse clinical group.
Keywords: discourse intervention; multilevel intervention; cognitive–communication; aphasia